1984
DOI: 10.1113/expphysiol.1984.sp002834
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion in Fetal Sheep and Its Relation to Sleep States and Breathing Movements

Abstract: SUMMARYSwallowing was recorded electromyographically in unanaesthetized fetal sheep in utero during the last third of gestation. In control fetuses bouts of swallowing were, on average, 2 0 min in duration and occurred at intervals of 2-31 h. Swallowing bouts were associated with a low-voltage electrocorticogram, eye movements and, in 82% of instances, with phasic activity in the dorsal neck muscles. These data indicate that fetuses are not in quiet (non-rapid eye movement; n.r.e.m.) sleep when swallowing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 16 publications
(29 reference statements)
2
33
0
Order By: Relevance
“…Absorption of digoxin by the fetus from amniotic fluid could occur by swallowing. However, fetal swallowing does not occur continuously, and intervals between swallowing have been reported to be as long as 2.31 h (20). Given the improbability that each fetus swallowed at the beginning of our study, swallowing is unlikely to be the only mechanism of digoxin absorption by the fetus from amniotic fluid.…”
Section: Discussionmentioning
confidence: 90%
“…Absorption of digoxin by the fetus from amniotic fluid could occur by swallowing. However, fetal swallowing does not occur continuously, and intervals between swallowing have been reported to be as long as 2.31 h (20). Given the improbability that each fetus swallowed at the beginning of our study, swallowing is unlikely to be the only mechanism of digoxin absorption by the fetus from amniotic fluid.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies also have demonstrated that fetal swallowing activity occurred in association with electrocortical activity and that alterations in fetal electrocortical activity may affect fetal swallowing by using intravenous injection of cholinergic antagonist atropine sulfate passing the blood-brain barrier vs. atropine methyl nitrate acting peripherally only in fetal sheep (28). Because fetal swallowing occurs predominantly during LV ECoG periods (14), change of the relative duration of LV periods may influence the swallowing rate. Although there was a small percentage of intermediate ECoG status in the fetus, which was not changed following the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal swallowing may be regulated by multiple factors, including dipsogenic stimulation, appetite, amniotic fluid availability, and behavioral status (3,14,21). In the present study, we used c-fos mapping technique to determine fetal central nervous activity that correlated to stimulated swallowing responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fetus can decrease metabolic requirements by reducing both the incidence and amplitude of breathing movements (Fowden et al 1989). These have been associated with a lower rate of lung liquid secretion and occurrence of fetal swallowing (Harding et al 1984;Moessinger et al 1990). Changes in fetal glucose homeostasis not only influence plasma concentrations of insulin (Bassett & Madill, 1974) but also concentrations of IGF.…”
Section: Maternal Nutrition and Fetal Growthmentioning
confidence: 99%